Population Outcomes of Three Approaches to Detection of Congenital Hearing Loss - Wake, Melissa (Pediatrics, 2016)
BACKGROUND: Universal newborn hearing screening was implemented worldwide largely on modeled, not measured, long-term benefits. Comparative quantification of population benefits would justify its high cost. METHODS: Natural experiment comparing 3 population approaches to detecting bilateral congenital hearing loss (>25 dB, better ear) in Australian states with similar demographics and services: (1) universal newborn hearing screening, New South Wales 2003–2005, n = 69; (2) Risk factor screening (neonatal intensive care screening + universal risk factor referral), Victoria 2003–2005, n = 65; and (3) largely opportunistic detection, Victoria 1991–1993, n = 86. Children in (1) and (2) were followed at age 5 to 6 years and in (3) at 7 to 8 years. Outcomes were compared between states using adjusted linear regression. RESULTS: Children were diagnosed younger with universal than risk factor screening (adjusted mean difference –8.0 months, 95% confidence interval –12.3 to –3.7). For children without intellectual disability, moving from opportunistic to risk factor to universal screening incrementally improved age of diagnosis (22.5 vs 16.2 vs 8.1 months, P < .001), receptive (81.8 vs 83.0 vs 88.9, P = .05) and expressive (74.9 vs 80.7 vs 89.3, P < .001) language and receptive vocabulary (79.4 vs 83.8 vs 91.5, P < .001); these nonetheless remained well short of cognition (mean 103.4, SD 15.2). Behavior and health-related quality of life were unaffected. CONCLUSIONS: With new randomized trials unlikely, this may represent the most definitive population-based evidence supporting universal newborn hearing screening. Although outperforming risk factor screening, school entry language still lagged cognitive abilities by nearly a SD. Prompt intervention and efficacy research are needed for children to reach their potential.